PENILAIAN EKUITAS PERUSAHAAN YANG MEMPUNYAI EMPLOYEE STOCK OPTION PLAN (ESOP): STUDI PADA PT WIJAYA KARYA (PERSERO) TBK. TAHUN 2011 - , Roby Lasmana ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Recently there are many companies in Indonesia that adopt the Employee Stock Option Plan (ESOP) as an equity-based compensation to give the right for employees to buy new shares. One of the state companies that adopt the ESOP is PT Wijaya Karya (Persero) Tbk. in which on June 6, 2011 the employees have converted some of the ESOP that they own. Outstanding ESOP which is a contingent equity will affect the company's equity value because it has the potential to provide a cash flow into the company and increase the amount of equity at the time of execution. This study aims to assess the equity value of PT Wijaya Karya (Persero) Tbk. in the year 2011 so that the results can be used not only by the shareholders but also the stakeholders. The analysis method used in this study is the income approach with discounted cash flow method-free cash flow to firm model (DCF-FCFF) and market approach with relative valuation method. The DCF method application is different from companies that have no outstanding ESOP, where there is a projection for equity addition from the execution of ESOP and outstanding ESOP valuation using option pricing method with the Black-Scholes model which is modified for assets that pay continuous dividends. The fair value of outstanding ESOP is used in the WACC calculation and reduces the firm value to get the equity value. The result of this study is an opinion of PT Wijaya Karya (Persero) Tbkâs equity fair market value in 2011 of Rp560,95/share. That result comes from a reconciliation of fair market value indication by an income approach of Rp582,12/share and by a market approach of Rp539,77/share.